The contribution of pilot entities to the implementation of the new public sector accounting system in Portugal - Nogueira, Sónia P. (2017)
The global financial crisis has emphasized the need for harmonized public sector accounts. Concerning accountability, transparency and sustainability several countries initiated reforms in public sector accounting. Across the world there has been a general trend for public sector accounting moving into accrual-based systems, supported by the International Public Sector Accounting Standards (IPSAS). In the institutionalization process, pilot entities seem to be strategically important to consider, especially in cases where the new system involves significant innovations. This paper introduces new theoretical arguments to explain, combining the new institutional theory with institutional logics. Using Portugal as an illustrative case, it addresses both the perspective of stakeholders and decision-makers. Main findings show that the use of pilot entities is acknowledged important mainly where prudence seems to be relevant to assure success in implementing accounting innovations. However, pilot entities must be offered enough means and support, so they can deal with the changes, offer relevant feedback to supervising bodies and express a more committed attitude towards the reforms.